2021
DOI: 10.7759/cureus.14374
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Proned Ventilation and Its Possible Association With Foot Drop: A Case Series

Abstract: The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus causing the coronavirus disease 2019 (COVID-19) pandemic is known to lead to the complicated sequelae of severe acute respiratory distress syndrome. Proning has been used as an adjunctive treatment to improve oxygenation in both ventilated and non-ventilated patients. Although patients respond well to this strategy, complications from this arise as well. It is hypothesized that COVID-19 intensive care unit (ICU) proned ventilation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 14 publications
0
19
0
3
Order By: Relevance
“…Approximately 75% of our subjects, most of them ventilated during intensive care, had abnormal MNC amplitude of the peroneal nerve. It was suggested that compressive unilateral peroneal neuropathy might result from unconventional use of prone ventilation, which is meant to improve oxygenation and reduce ventilatory lung injury [ 29 ]. Upper limb nerves, e.g., the ulnar nerve, were also found to be affected by prolonged prone positioning during ventilation [ 6 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 75% of our subjects, most of them ventilated during intensive care, had abnormal MNC amplitude of the peroneal nerve. It was suggested that compressive unilateral peroneal neuropathy might result from unconventional use of prone ventilation, which is meant to improve oxygenation and reduce ventilatory lung injury [ 29 ]. Upper limb nerves, e.g., the ulnar nerve, were also found to be affected by prolonged prone positioning during ventilation [ 6 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malik et al 33 found that a significant majority (83.3%) of their patients who were identified with a focal neuropathy had a history of at least one prone positioning session in the acute care hospital. Chang et al 34 presented patients who presented with unilateral ankle dorsiflexion weakness to their acute rehabilitation facility were all managed with ICU proned ventilation. Finally, Brugliera et al 15 described a variety of peripheral nerve injuries in patients after extended prone position ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 For example, the prone positioning intervention has been recommended for 12 to 16 hours per day in mechanically ventilated adults with COVID-19 and refractory hypoxemia 24 , but has associated with increase rates of acquired peripheral PNIs. [6][7][8][10][11][12] Given the ongoing COVID-19 pandemic, and risks of new variants causing a resurgence of hospital admissions, further attention should be paid to the long-term sequela including PNIs. These injuries require long-term follow up and care with therapy and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Malik et al described the first case series of COVID-19 PNIs in 12 patients admitted to an inpatient rehabilitation 8 , which has subsequently been reaffirmed by several other published case series in survivors of severe COVID-19. [9][10][11][12] The anatomical distribution of PNIs implies a role for mechanical forces as these localizations mirror sites known to be vulnerable to compression and/or traction 6,7 Unfortunately, the recovery from PNI is notoriously slow and frequently incomplete in the general population 13 , and the demographics of severe COVID-19 patients include enrichment of known risk factors for worse outcomes after PNI such as advanced age, obesity and diabetes mellitus. 8 There is little doubt that acquired PNIs contribute to long term disability in survivors of severe COVID-19 with reported incidences between 14.5-16%.…”
Section: Introductionmentioning
confidence: 99%